ENHANCING PERSONAL AND FAMILY FINANCE COURSES USING CASE STUDIES. - Gudmunson, Clinton G.; ZUIKER, VIRGINIA SOLIS; KATRAS, MARY JO; SABRI, MOHAMAD FAZLI (College Student Journal)
Growing financial concerns among college students and on college campuses suggests urgency in teaching personal finance more effectively. Active learning approaches to teaching, including the use of case studies, problem-based learning, group work, in-class writing, demonstrations, and so forth, may be more appropriate and useful when used to teach topics that are clearly applied and have immediate relevance in students' personal and family lives. One objection to active learning approaches, however, is that that some students prefer, or have an aptitude for traditional lecture and passive learning, i.e. the "aptitude problem." We sampled 138 students in a personal finance course taught at a large public university in the Midwest. Findings from hierarchical regressions demonstrate that aptitude for traditional lecture formats can be overcome if students view active learning as non-redundant, interesting, and promoting a positive group encounter utilizing a case study approach. [142 words]